Thrombocytopaenia during nintedanib treatment in a patient with idiopathic pulmonary fibrosis. Issue 7 (16th July 2020) - Ochi, Yusuke; Kato, Motoyasu; Fujioka, Masahiro; Hayashi, Mika; Takagi, Haruhi; Takahashi, Kazuhisa
Abstract: A 72‐year‐old Japanese man was diagnosed with idiopathic pulmonary fibrosis (IPF), and treatment with nintedanib was initiated. Ten months after nintedanib treatment initiation, his serum platelet levels gradually decreased until it reached 14, 000/mm 2 and he was admitted to our hospital. At admission, his serum platelet‐associated immunoglobin G level was markedly increased, and bone marrow biopsy showed megakaryocytic hyperplasia. We suspended nintedanib treatment and transfused platelet concentrate. In the absence of evidence of other diseases related to thrombocytopaenia, including Helicobacter pylori infection, thrombocytopaenia was considered to have been caused by nintedanib use. After the patient received high‐dose dexamethasone therapy (20 mg/day for four days) and thrombopoietin receptor agonist, eltrombopag olamine (maximum dose: 50 mg/day), the serum platelet count gradually increased. Here, we present a rare case of symptomatic thrombocytopaenia associated with nintedanib treatment in a patient with IPF. Abstract : We present a rare case of symptomatic thrombocytopaenia associated with nintedanib treatment in a patient with idiopathic pulmonary fibrosis (IPF).